Taking the twinkle out of starlight. - Lloyd-Hart, M. (IEEE spectrum)
The article discusses the technology called adaptive optics used in improving telescopes, enabling astronomers to capture clear, sharp images of the galaxies, stars, and planets that populate the universe. The technique brings together the latest in computers, materials science, electronic detectors, and digital control in a system that warps and bends a mirror in the telescope to counteract, in real time, the atmospheric distortion. An adaptive optics system installed on the 6.5-meter-diameter telescope, called the MMT telescope, on Mt. Hopkins, south of Tucson, Arizona, takes the technology a step further. The ways by which adaptive optics overcomes the deficiencies of conventional telescopes with the design and structure of the adaptive secondary mirror and the use of ing interferometry are discussed.